2019
DOI: 10.1016/j.devcel.2019.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Processing of Two Mechanosensory Modalities by a Single Neuron in C. elegans

Abstract: Neurons convert synaptic or sensory inputs into cellular outputs. It is not well understood how a single neuron senses, processes multiple stimuli, and generates distinct neuronal outcomes. Here, we describe the mechanism by which the C. elegans PVD neurons sense two mechanical stimuli: external touch and proprioceptive body movement. These two stimuli are detected by distinct mechanosensitive DEG/ENaC/ASIC channels, which trigger distinct cellular outputs linked to mechanonociception and proprioception. Mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(126 citation statements)
references
References 66 publications
6
119
1
Order By: Relevance
“…, 2019 ) and that physical deformations are correlated with calcium transients. Similarly, movement induces localized calcium transients in the tertiary dendrites of the Caenorhabditis elegans PVD proprioceptors that depend on expression of a DEG/ENaC/ASIC protein ( Tao et al. , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…, 2019 ) and that physical deformations are correlated with calcium transients. Similarly, movement induces localized calcium transients in the tertiary dendrites of the Caenorhabditis elegans PVD proprioceptors that depend on expression of a DEG/ENaC/ASIC protein ( Tao et al. , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cell DVA has been shown to exhibit proprioceptive properties with a dependence on a mechanosensitive channel, TRP-4, which acts as a stretch receptor to regulate the body bend amplitude during locomotion (41). In the case of PVD, a recent study (42) has revealed that body stretches induce local dendritic calcium transients in PVD and dendritic release of a neuropeptide NLP-12 which appears to regulate the amplitude of sinusoidal body movements. However, whether these proprioceptive feedback systems contribute to locomotory rhythm generation remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Together, the PVD and FLP neurons comprise a sensory network of the entire body that responds to harsh mechanical stimuli (Way and Chalfie, 1989). PVD and FLP neurons show some differences in function and morphology: PVD neurons sense hot and cold temperature, high osmolarity and play a role in proprioception, whereas FLP neurons sense noxious high temperatures and humidity (Chatzigeorgiou et al, 2010;Albeg et al, 2011;Mohammadi et al, 2013;Cohen et al, 2014;Tao et al, 2019). Also, PVD is morphologically unciliated while FLP is ciliated (Ward et al, 1975;Altun and Hall, 2011).…”
Section: Dendritic Branching: a Multi-protein Ligand-receptor Complexmentioning
confidence: 99%